Pembinaan Remaja Melalui Sosialisasi Pendewasaan Usia Perkawinan di SMA Negeri 1 Suela - Fahruddin Fahruddin; Muhamad Farid; Nindy Nursilva Parizka; Muhammad Ihsan Kadafi (Unram Journal of Community Service, 2021)
Suntalangu village is one of the villages in the Suela Subdistrict of East Lombok Regency. The population of Suntalangu Village, based on the data from the past few years, was 7.754 people, with 2.540 families. Problems often encountered in Lombok, especially in Suntalangu Village, namely Early Childhood Marriage (Merarik Kodeq). It’s due to several factors, one of which is lack of awareness and lack of information to adolescents about the importance of maturation of the age of marriage. The KKN implementation for 45 days aims to increase adolescent awareness about the importance of Maturation of The Age of Marriage (PUP). This is done by running the main program, namely socialization on Maturation of Marriage Age by the Office of Women Empowerment of Child Protection and Family Planning (DP3AKB) in State High School 1 Suela District Suela East Lombok Regency. From this activity, it is expected that teenagers begin to pay attention to the importance of the Maturation of Marriage Age in order to create a prosperous Indonesian Family